Optimized dualCEST-MRI for imaging of endogenous bulk mobile proteins in the human brain - Breitling, Johannes; Paech, Daniel; Ladd, Mark E.; Bachert, Peter (NMR in biomedicine, 2020)
Dual-frequency irradiation chemical exchange saturation transfer (dualCEST) allows imaging of endogenous bulk mobile proteins by selectively measuring the intramolecular spin diffusion. The resulting specificity to changes in the concentration, molecular size, and folding state of mobile proteins is of particular interest as a marker for neurodegenerative diseases and cancer. Until now, application of dualCEST in clinical trials was prevented by the inherently small signal-to-noise ratio and the resulting comparatively long examination time. In this study, we present an optimized acquisition protocol allowing 3D dualCEST-MRI examinations in a clinically relevant time frame. The optimization comprised the extension of the image readout to 3D, allowing a retrospective co-registration and application of denoising strategies. In addition, cosine-modulated dual-frequency presaturation pulses were implemented with a weighted acquisition scheme of the necessary frequency offsets. The optimization resulted in a signal-to-noise ratio gain by a factor of approximately 8. In particular, the application of denoising and the motion correction were the most crucial improvement steps. In vitro experiments verified the preservation of specificity of the dualCEST signal to proteins. Good-to-excellent intra-session and good inter-session repeatability was achieved, allowing reliable detection of relative signal differences of about 16% or higher. Applicability in a clinical setting was demonstrated by examining a patient with glioblastoma. The optimized acquisition protocol for dualCEST-MRI at 3 T enables selective imaging of endogenous bulk mobile proteins under clinically relevant conditions.
Gesehen am 06.08.2020